2008
DOI: 10.1002/bem.20458
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of radiation emitted by cellular phones: The influence of exposure side and time

Abstract: This study examined the time dependence effects of exposure to radiofrequency radiation (RFR) emitted by standard GSM cellular phones on the cognitive functions of humans. A total of 48 healthy right-handed male subjects performed a spatial working memory task (that required either a left-hand or a right-hand response) while being exposed to one of two GSM phones placed at both sides of the head. The subjects were randomly divided into three groups. Each group was exposed to one of three exposure conditions: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 28 publications
1
37
0
3
Order By: Relevance
“…Luria et al 9 observed significantly higher response time among radiation-exposed group than nonexposed. Similarly, we also observed that vitality, emotional, and mental health status are significantly lower in persons exposed to high and medium level of radiations as compared with people exposed to low level of radiation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Luria et al 9 observed significantly higher response time among radiation-exposed group than nonexposed. Similarly, we also observed that vitality, emotional, and mental health status are significantly lower in persons exposed to high and medium level of radiations as compared with people exposed to low level of radiation.…”
Section: Discussionmentioning
confidence: 94%
“…Right-handed subjects exposed to RFR on the left side of their head, on average, had significantly longer response times when compared with exposure to the right side and sham exposure. 9 Largest study of its kind ever; the 13 nation interphone project in 2012, claimed that for an average user (cell phone use for 2 hours a month), increase in cancer cases is not significant. 10 Reevaluation of the Interphone study by a group of eminent scientists has found that even for average users, increase in brain tumor is significant for greater than 10 years of use, indicating some risk of carcinogenicity.…”
Section: Reflex [Risk Evaluation Of Potential Environmental Hazards Fmentioning
confidence: 99%
“…W pracach późniejszych, w miarę poprawiania się metodyki badań dotyczących tego problemu, coraz częściej nie stwierdzano żad-nych efektów oddziaływania PEM telefonii komórko-wej na procesy poznawcze. Takie wnioski przedstawiono w większości prac z ostatnich lat [27,28,36,49,[72][73][74].…”
Section: Wpływ Pem Na Układ Krążenia I Jego Regulacjęunclassified
“…[73] stwierdzili wydłużenie się czasu reakcji prawej ręki w teście operacyjnej pamię-ci przestrzennej u osób eksponowanych na PEM, któ-rego źródłem był telefon usytuowany przy lewym uchu, jednak następne badanie tego samego zespołu [69] wykluczyło, żeby efekt ten był wynikiem wpływu mikrofalowych PEM. Autorzy wskazali na nagrzewanie się telefonu lub działanie słabych PEM o niższych czę-stotliwościach, emitowanych przez elektronikę telefonu, jako potencjalne przyczyny obserwowanego efektu.…”
Section: Wpływ Pem Na Układ Krążenia I Jego Regulacjęunclassified
“…The authors in [38] concluded that the duration of exposure to EM radiation from a standard GSM mobile phone had an effect on the cognitive functions of humans. It has been shown in [39] that whole-body exposure to a SAR of 4 W/kg for 20-30 minutes resulted in a body increase in temperature of up to 0.5…”
Section: /(Distance)mentioning
confidence: 99%